Evaluation of the antihypertensive angiotensin-converting enzyme inhibitory (ACE-I) activity and other probiotic properties of lactic acid bacteria isolated from traditional Greek dairy products. (December 2017) - Georgalaki, Marina; Zoumpopoulou, Georgia; Mavrogonatou, Eleni; Van Driessche, Gonzalez; Alexandraki, Voula; Anastasiou, Rania; Papadelli, Marina; Kazou, Maria; Manolopoulou, Eugenia; Kletsas, Dimitris; Devreese, Bart; Papadimitriou, Konstantinos; et al.
Abstract: The technological and probiotic potential of lactic acid bacteria isolated from artisanal Greek yoghurt and fermented milks were evaluated. Fifty-three strains were identified by rep-PCR and 16S rDNA sequencing to belong to different Lactobacillus or Enterococcus spp., as well as to Streptococcus thermophilus and Lactococcus lactis . Several strains exhibited promising technological and probiotic properties. Among them, we focused on the production of bioactive peptides with angiotensin-converting enzyme inhibitory (ACE-I) activity during milk fermentation. The majority of strains produced ACE-I peptides when grown in skimmed milk. ACE-I peptides were sometimes sequestered in the original fermented milk sample, but were released and detected following high performance liquid chromatography (HPLC) purification. Mass spectrometry analysis of major peptide peaks in HPLC fractions with ACE-I activity revealed that they derived from the N- or C-terminal of the isracidin peptide region of αS1 -casein and two internal peptide fragments, one from β-casein and one from κ-casein.